2014
DOI: 10.5152/tjbh.2014.1777
|View full text |Cite
|
Sign up to set email alerts
|

Cinical Significance of Androgen Receptor, CK-5/6, KI-67 and Molecular Subtypes in Breast Cancer

Abstract: Objective: To detect the relationship between molecular subtypes of breast cancer with expressions of androgen receptor, cytokeratin 5/6 (CK5/6)and Ki-67. Materials and Methods:Expressions of androgen receptor, CK-5/6 and Ki-67 were determined by immunohistochemistry in paraffin-embedded sections obtained from 86 invasive breast cancer cases of stages I/IIa/IIb in 4 molecular subtypes. Patients treated for recurrent disease and locally advanced disease were excluded. Results:Forty one luminal A cases, ie. posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The most detected tumor type was invasive ductal carcinoma (89.9%). This result was consistent with some literatures [3,6,7] and inconsistent with some of the literature with the largest population of breast cancer series [1,8]. 623 and 380 patients were included in these two published studies, respectively, and they found tumor type-histology was significantly related to ALM (p<0.001 and p=0.003, respectively).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The most detected tumor type was invasive ductal carcinoma (89.9%). This result was consistent with some literatures [3,6,7] and inconsistent with some of the literature with the largest population of breast cancer series [1,8]. 623 and 380 patients were included in these two published studies, respectively, and they found tumor type-histology was significantly related to ALM (p<0.001 and p=0.003, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Hormonal receptor status and Ki-67 proliferation index are studied for biological behavior of primary tumor [3]. Related to ER, PR, HER2, and Ki-67 index, molecular subtypes LA, LB, HER2 positive, and TN are formed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High Ki 67 expression is associated with higher histologic grade, larger tumor size, positive lymph node status, short disease-free survival, and overall survival in breast cancer [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
“… 11 – 15 Many authors have reported significant associations between AR expression by cancer cells and improved overall survival and disease-free survival. 16 21 In addition, targeted therapy blocking AR receptors is being developed, and researchers are trying to better understand the molecular signaling pathways by which androgens alter the proliferation of cancer cells. It may be the only endocrine therapy available to a subset of patients with the aggressive triple negative tumors that lack the expression of ER, PR, and HER-2/neu, and hence, are unable to respond to targeted therapy.…”
mentioning
confidence: 99%